The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1111/j.1530-0277.1992.tb00649.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Co‐Morbid Alcoholic Men: A 1‐Year Follow‐Up

Abstract: In this prospective, 1-year study, 360 males admitted to an inpatient alcoholism treatment program were administered a DSM-III compatible structured interview and subtyped by co-occurring psychiatric disorder. Forty percent satisfied diagnostic criteria for alcohol dependence while 27% met criteria for alcohol dependence and one additional psychiatric syndrome. The dually diagnosed patients were divided into: alcohol dependence plus drug abuse, alcohol dependence plus antisocial personality and alcohol depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
1
8

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(65 citation statements)
references
References 15 publications
2
54
1
8
Order By: Relevance
“…The Childhood Deviance Scale correlated signifi cantly with comparable items collected 10 or 20 years earlier, such as the Childhood Conduct Disorder Scale (r = .56, p < .0001) and the School Teacher Questionnaire Behavioral Summary Score (r = .37, p < .0001) (Knop et al, 2009). The Psychosocial Interview also collected extensive data about the quantity and frequency of the consumption of beer, wine, and distilled spirits in the recent past and included the 32-item Alcoholism Severity Scale used in other studies by our group (Penick et al, 1987;Powell et al, 1992) to evaluate the major symptoms of alcoholic drinking both in the past year and over the subject's lifetime.…”
Section: Adult Outcome Measuresmentioning
confidence: 99%
“…The Childhood Deviance Scale correlated signifi cantly with comparable items collected 10 or 20 years earlier, such as the Childhood Conduct Disorder Scale (r = .56, p < .0001) and the School Teacher Questionnaire Behavioral Summary Score (r = .37, p < .0001) (Knop et al, 2009). The Psychosocial Interview also collected extensive data about the quantity and frequency of the consumption of beer, wine, and distilled spirits in the recent past and included the 32-item Alcoholism Severity Scale used in other studies by our group (Penick et al, 1987;Powell et al, 1992) to evaluate the major symptoms of alcoholic drinking both in the past year and over the subject's lifetime.…”
Section: Adult Outcome Measuresmentioning
confidence: 99%
“…Others question the overall relevance of subgroups, believing that high levels of psychiatric symptoms are inherent in alcohol-dependent individuals, even when sober (28). Yet other research challenges the belief that affective disturbances of any type are related to the clinical outcome, and there are disagreements about the optimal way to identify and characterize potentially substanceinduced disorders (26,(29)(30)(31).…”
mentioning
confidence: 99%
“…In one of the Indian studies (26), it was reported that substance use is confined to tribal females, those of lower socio-economic status. Other studies too have reported their patient population as belonging to lower middle and lower class and being employed (17,18). The majority of female patients in the current study belonged to the lower socio-economic class (68%), rural background (62%), and worked as daily wage laborers (64%) either in factories or agricultural fields.…”
Section: Discussionmentioning
confidence: 53%
“…Mean age at presentation in various studies have ranged between 35 and 46 years (15)(16)(17)(18). Two earlier studies (19,20) usually in their fourth decade of life and later compared to males.…”
Section: Discussionmentioning
confidence: 99%